Sinclair Lewis: The One And The Other - Ms. M.Valarmathi; Dr.K.N . Sharmila (Revista Electronica de Veterinaria)
Sinclairdewis, the American novelist of the 1920’s is essentially a critic of Social life. Man’s duty as a responsible gen of the society where he lives is coloured by a spectrum of social imagination. Man is the product of society from the very beginning of the existential predicament in his home far away from his Home, the heavenly abode . Man’s Success and failure depend mostly on the type of life he follows, imbibing the cultural traits, Customs and practices of the spirit of the time represented as the ‘spirit zeist’ peculiar to each society . Man cannot live in a vacuum, devoid of Social presence and Social awareness . So a closer analysis of Lewis’s novels yields rich dividends to an enterprising critic to conclude that ‘man is nothing if not social’. The social imagination of the novelist is exploited in the present study title, "Sinclain Lewis: The one and the other”.